ANALISIS TARIF PREMI DAN ASUMSI LOADING PADA PRODUK ASURANSI DWIGUNA BEASISWA - Ira Rosianal Hikmah; Yulial Hikmah (Diponegoro University, 2020)
Based on data from Badan Pusat Statistik (BPS), the number of Indonesia's population has consistently increased every year. This will cause several problems, one of them is public health. Health problems that occur cause some risks that cause losses. Therefore, one way to reduce the impact of these risks is insurance. This study analyzes how the process of forming premium prices with loading assumptions that are in accordance with existing assumptions in order to meet the criteria of equitable to the client, deliverable by the agent, and profitable to the company. This research uses a quantitative research approach. The population in this study was all Sum Insured (SI) while the sample was 1000 SI male sex. The data used in this study are secondary data that is data from an ABC insurance company in Indonesia, literature study through books, journal references, and previous research. The results of this study are the calculation of premiums by the methods used by the company more efficiently when compared with formulas in accordance with the theory. Although the price of a premium is more expensive using the company method, it is not significantly different. If using the company method, the sum insured used is the sum insured from death benefit whereas the theory is the average of claims incurred at that age. The fees charged are still fairly reasonable in accordance with the rules of setting the price of insurance premiums. In addition, the use of CSO 80 tables and Reinsurance Rates that have been adjusted to the company's interest rate of 5% in accordance with the expected cash value desired by the company.